2021
DOI: 10.3390/ijerph19010314
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Predisposition to Post-Traumatic Stress Disorder Development—The Role of Neuropeptides

Abstract: Post-traumatic stress disorder (PTSD) is characterized by re-experiencing a traumatic event, avoidance, negative alterations in cognitions and mood, hyperarousal, and severe functional impairment. Women have a two times higher risk of developing PTSD than men. The neurobiological basis for the sex-specific predisposition to PTSD might be related to differences in the functions of stress-responsive systems due to the interaction between gonadal hormones and stress peptides such as corticotropin-releasing factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 127 publications
(155 reference statements)
0
6
0
1
Order By: Relevance
“…[20] Studies have shown that women are twice as likely as men to develop posttraumatic stress disorder. [21] Gender, as an unchangeable factor, requires healthcare professionals to pay more attention to the psychological problems that may arise in female myocardial infarction patients in their clinical work and to actively take effective measures to eliminate the negative emotions of female patients, so as to reduce the risk of PTSD in female myocardial infarction patients.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Studies have shown that women are twice as likely as men to develop posttraumatic stress disorder. [21] Gender, as an unchangeable factor, requires healthcare professionals to pay more attention to the psychological problems that may arise in female myocardial infarction patients in their clinical work and to actively take effective measures to eliminate the negative emotions of female patients, so as to reduce the risk of PTSD in female myocardial infarction patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, a sudden rise in the number of critically ill patients and the burden of decision-making affected stress and anxiety. Some studies have reported the incidence of PTSD following a sense of uncertainty and fear of disease transmission to oneself and others [ 31 , 34 ]. These findings are similar to previous research which found that coping was a significant mediator among stressors such as fear of COVID-19 on depression and anxiety in a sample of nurses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that females are more likely to show higher emotional disorders when stimulated by the same negative things as males. Women are twice as likely as men to develop symptoms of PTSD, and the reason may be due to interactions between sex hormones and stress peptides, the study said (21). In addition, due to the difference in sex hormones (22), women are more sensitive to painful stimuli and are more likely to perceive physical and mental harm brought by diseases.…”
Section: Discussionmentioning
confidence: 99%